Metode Presentasi Untuk Membangun Keterampilan Public Speaking Dan Kepercayaan Diri Siswa Dalam Pembelajaran PAI di SMAN 1 Mojotengah Wonosobo - Nita Astuti; Rifqi Muntaqo; Nur Farida (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Speaking skills require students to be able to communicate with other students. Many students still have difficulty speaking in public. They may not even be confident in expressing ideas or opinions either in class or in public. Therefore, in Islamic religious education, students must be trained in public speaking skills and self-confidence. This can be achieved at school by using the presentation method of learning public speaking.To build students' public speaking skills and self-confidence by using presentation methods in the Islamic religious education learning process, there needs to be support from various school components, especially teachers, in carrying out learning in class.1. This research focuses on discussing presentations in building student public speaking which focuses on what is the concept of presentation methods in learning Islamic religious education at SMAN 1 Mojotengah Wonosobo? 2. What are the teacher's efforts to build students' public speaking skills and self-confidence in learning PAI at SMAN 1 Mojotengah Wonosobo? 3. How do you apply the presentation method to build public speaking and students' self-confidence in learning Islamic character religious education at SMAN 1 Mojotengah Wonosobo?The research method for this research is field research or field research, which is a research approach used to obtain concrete data in field research. The type of research used in this research is qualitative research. Research that aims to describe and analyze social actions, events, phenomena, attitudes, beliefs, perceptions and thoughts of individuals both individually and in groups is known as qualitative research. Some descriptions are used to discover principles and explain what leads to conclusions.